Detecting Adverse Drug Reaction (ADR) with data mining and predicting its intensity with machine learning - Hussain, Nadib; Islam, Tanvir; Apu, Rafik Un Nabi (BRAC University, 2018)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2018.